Effects of combined Pulsed Dye Laser and Fractional CO2 Laser treatment of burn scars and correlation with plasma levels of collagen type I, MMP-2 and TIMP-1. Issue 6 (September 2021) - Matuszczak, Ewa; Weremijewicz, Artur; Koper-Lenkiewicz, Olga Martyna; Kamińska, Joanna; Hermanowicz, Adam; Dębek, Wojciech; Komarowska, Marta; Tylicka, Marzena
Highlights: Combined PDL and AFCL treatment is safe. CO2-AFL treatment for burn scars improve texture, colour, function and alleviate pruritus. Decrease of plasma MMP2 TIMP1 and collagen I after laser treatment reflects reduced dynamic of scar. Abstract: Hypertrophic burn scars remain a significant burden for patients and a challenge for clinicians. The aim: Assessement of the efficacy of combined Pulsed Dye Laser and Ablative Fractional CO2 Laser therapy on hyperthophic scars and correlation with plasma levels of MMP-2, TIMP-1 and alpha-1 type I collagen. Patients and methods: Twenty five pediatric subjects were enrolled into the study. Control group consisted of age-matched subjects admitted for surgical repair of inguinal hernia. For the assessment of the results of laser treatment we used the Vancouver scar scale (VSS), and Patient-Observer Scar Assessment Scale (POSAS). We also correlated clinical results with plasma levels of MMP-2, TIMP-1 and alpha-1 type I collagen. Results: All subjects reported the laser treatment resulted in improvement and were somewhat satisfied or very satisfied with their experience. No adverse events were reported. The levels of MMP-2, TIMP-1 and alpha-1 type I collagen in our patients with scars before laser threatment were higher in comparison to controls. We also found statistically significant decrease in the levels of MMP-2, TIMP-1 and alpha-1 type I collagen after laser treatment of burn scars Conclusions: Our study clearly shows that combined CO2-AFL treatment for burn scars improve texture, colour, function and alleviate pruritus. We believe that decrease in the levels of MMP-2, TIMP-1 and alpha-1 type I collagen after laser treatment of burn scars, reflects reduced dynamic of scar.